2021
DOI: 10.1111/bph.15371
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia‐induced miR‐342‐5p down‐regulation exacerbates neonatal bronchopulmonary dysplasia via the Raf1 regulator Spred3

Abstract: Background and Purpose Bronchopulmonary dysplasia (BPD) is the most prevalent chronic paediatric lung disease and is linked to the development of chronic obstructive pulmonary disease. MicroRNA‐based regulation of type II alveolar epithelial cell (T2AEC) proliferation and apoptosis is an important factor in the pathogenesis of BPD and warrants further investigation. Experimental Approach Two murine models of hyperoxic lung injury (with or without miR‐342‐5p or Sprouty‐related, EVH1 domain‐containing protein 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…LTBR expression was also increased by hyperoxia-stimulated A549 and ATII cells in this study. Apoptosis of ATII is observed in hyperoxiastimulated BPD model [19]. Our work supports that hyperoxia decreases cell viability and promotes apoptosis in A549 and ATII cells.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…LTBR expression was also increased by hyperoxia-stimulated A549 and ATII cells in this study. Apoptosis of ATII is observed in hyperoxiastimulated BPD model [19]. Our work supports that hyperoxia decreases cell viability and promotes apoptosis in A549 and ATII cells.…”
Section: Discussionsupporting
confidence: 85%
“…Despite studies on LTBR in lung development or lung cancer [9,26,27], its role in BPD remains unknown. We used a mouse model of BPD by exposure to 100% O 2 on postnatal day 4 followed by recovering for 10 days [19] and found that LTBR expression was increased in lungs of BPD mouse model compared with normal control mice. ATII cells are pulmonary epithelial progenitor cells and exist in the corners of alveoli, taking up only 5% of alveolar surface area in healthy adults with many functions including synthesizing and secreting surfactants, transporting intrapulmonary fluid and ion, supporting immune modulation, and regenerating alveolar epithelium after injury [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, none of the differentially expressed miRs have thus far been found to be directly associated with PAH pathology. Nevertheless, some of the miRs that are found to be affected in PAH EVs are known to be involved in other lung diseases; for example, miR-342, found to be down-regulated in PAH EVs in the present study, has been shown to exacerbate neonatal broncho-pulmonary dysplasia [ 32 ]. Likewise, miR-486 carrying EVs was more recently exhibited to promote angiogenesis after myocardial infarction in mice [ 18 ], whereas miR-26a, found to be upregulated in the present study, was identified as inhibiting angiogenesis in a cellular model of hepatic carcinoma [ 33 ].…”
Section: Discussionmentioning
confidence: 99%